Determination and Validation of Nitrite and Nitrate Levels in Drinking Water from Various Sources in Medan City Using Visible Spectrophotometry - Malau, Chienley P; Manik, Boy; Zai, Reni Durti (CV. Nusantara Scientific Medical, 2025)
The maximum allowable concentrations of nitrite and nitrate in drinking water are regulated by the Regulation of the Ministry of Health of the Republic of Indonesia No. 492/Menkes/Per/IV/2010. Variations in environmental conditions and agricultural activities may influence the levels of these contaminants in different water sources. This study aimed to determine nitrite and nitrate concentrations in drinking water obtained from several sources in Medan City. Eight samples were collected, consisting of municipally treated water from two drinking water companies, two well water samples, two commercially bottled water brands, and boiled well water. Quantitative analysis was performed using visible spectrophotometry at a wavelength of 536 nm with a Shimadzu UV mini-1240 spectrophotometer. Nitrite concentrations ranged from 0.0273 to 0.6452 mg/L, while nitrate concentrations ranged from 0.0148 to 3.9431 mg/L. All measured levels were below the maximum permissible limits. The validated analytical method demonstrated acceptable accuracy and precision, indicating its suitability for routine monitoring of drinking water quality. Differences in water source and management practices were found to influence nitrite and nitrate concentrations.